Study of the addition of natural antioxidant in butter (Research, Society and Development, 2020)
Butter is a product with reduced shelf life because of the oxidation of lipids, homewever the lipid degradation can be inhibited through the action of natural or synthetic antioxidants.  Propolis is a natural substance produced by bees and recognized for its bioactive potential. This work aimed to evaluate the antioxidant capacity of the alcoholic solution of propolis as a natural preservative in the butter. The samples (A) control, (B) butter with própolis extract 100 ppm, (C) butter with própolis extract 200 ppm and (D) butter with butylated hydroxytoluene (BHT) were submited to accelerated oxidative stability tests (Schaal Oven Test), physical-chemical analyzes, microbiologicals and sensorial tests. The peroxide index analysis showed similar efficiency between the use of BHT and propolis in samples C and D. Samples A and C presented a high frequency of responses in the acceptance range, however the sample A exhibited the highest percentage of preference for analystis. The purchase intention tests showed a percentage of positive responses greater than 50% for both samples. We concluded that própolis may play an effectively role as an antioxidant in butter, nevertheless the form of alcoholic extract adds sensory characteristics that alter the flavor of the product.